Gamer's health guide: Optimizing performance, recognizing hazards, and promoting wellness in esports - Emara, A. K.; Ng, M. K.; Cruickshank, J. A.; Kampert, M. W.; Piuzzi, N. S.; Schaffer, J. L.; King, D. (Current Sports Medicine Reports, 2020)
Electronic sports (esports), or competitive video gaming, is a rapidly growing industry and phenomenon. While around 90% of American children play video games recreationally, the average professional esports athlete spends 5.5 to 10 h gaming daily. These times and efforts parallel those of traditional sports activities where individuals can participate at the casual to the professional level with the respective time commitments. Given the rapid growth in esports, greater emphasis has been placed on identification, management, and prevention of common health hazards that are associated with esports participation while also focusing on the importance of health promotion for this group of athletes. This review outlines a three-point framework for sports medicine providers, trainers, and coaches to provide a holistic approach for the care of the esports athlete. This esports framework includes awareness and management of common musculoskeletal and health hazards, opportunities for health promotion, and recommendations for performance optimization.